1986
DOI: 10.1111/j.1365-2923.1986.tb01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to curriculum planning

Abstract: This booklet describes different ways used to tackle the problem of curriculum planning. By studying these approaches teachers can get an insight into the process in their own school. First they must decide whether there should be a particular focus for curriculum planning and if so what it should be. In the light of this they can modify their school's approach. To what extent do they wish to focus on: aims and objectives (engineering approach), teaching methods (mechanics approach), content (cookbook approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 4 publications
(5 reference statements)
0
43
0
1
Order By: Relevance
“…Across a three-year period, the Workgroup discussed and developed a variety of curricular designs (Harden, 1986;Schubert, 1986) that could be implemented in a timeconstrained training environment.…”
Section: Development Of the Health Education Curriculummentioning
confidence: 99%
“…Across a three-year period, the Workgroup discussed and developed a variety of curricular designs (Harden, 1986;Schubert, 1986) that could be implemented in a timeconstrained training environment.…”
Section: Development Of the Health Education Curriculummentioning
confidence: 99%
“…This was also associated with the development of new concepts such as "problem-based learning," "student-centered learning," "community-based curriculum," and "integrated teaching." 10 Harden et al identified six educational strategies related to the curriculum in a medical school. 11 Each of these is presented as a spectrum.…”
Section: Procedures or Methodsmentioning
confidence: 99%
“…This approach, as Harden commented, concentrates on details at the expense of the overall picture. 10 It ignores an overall strategy, and the criteria for selection of contents are often not clear, and may be related either to the interest of people planning the curriculum, or to the influence of the different departments in the college. This last point is of particular importance in deciding the percentage of time devoted to each subject.…”
Section: Evaluation Of the Current Curricula In Saudi Medical Collegesmentioning
confidence: 99%
“…D esde que Harden demostró que la formación médica se encuentra centrada en disciplinas parceladas y en la atención hospitalaria, la discusión sobre la formación generalista es importante 1,2 : algunos autores abogan por un modelo emergente de educación médica para Latinoamérica, caracterizado por un dominio selectivo de los conocimientos básicos, por la comprensión de la conducta biopsicosocial, prevención y la salud comunitaria en igual importancia que los aspectos curativos 3,4 . Se ha abogado por introducir las ciencias sociales en la educación médica, siendo la principal tarea del pregrado exponer la determinación de la salud 5 .…”
unclassified